Kajian Patofisiologis Gejala Klinis dan Psikososial Sebagai Dampak Gangguan Fungsi Tiroid pada Wanita Usia Produktif - Mutalazimah, Mutalazimah; Mulyono, Budi; Murti, Bhisma; Azwar, Saifuddin (Jurnal Kesehatan, 2013)
Indonesia has not been free from iodine deficiency, demonstrated by the increased prevalence oftotal goitre rate (TGR) from 9.8% in 1998, to 11.1% in 2003. New problem that occurs in endemic areas ofiodine deficiency is the presence of iodine excessive, one of them as the impact of universal salt iodizationprogram (USI) and iodiol supplementation in a long period of time. Both deficiency and excessive of iodinecan result in thyroid dysfunction. Impaired thyroid function is manifest broadly on biopsychosocial aspects,which is detrimental especially for childbearing women, as a determinant of survival and quality of life forfuture generations. Based on the measurement of TSH and FT4, were childbearing women who suffersubclinical hypothyroidism were 2%, subclinical hyperthyroidism were 26% and euthyroid were 76%.Biopsychosocial characteristics that can be described from hypothyroid subjects are visible goiter, puffyface, dry skin, fatigue, decreased concentration, menorrhagia, easily upset, depressed, apathetic and withdrawn.Meanwhile, the varying percentage of subjects with subclinical hyperthyroidism showed signs andsymptomsinclude a palpablegoiter,heat intolerance, exophthalmos, tiredness, pritibial edema, muscleweakness,delicated skin, poor memory,decreased concentration, menstrual disorders, decreased sexuallibido,anxiety,sleep disturbances, irritability,decreased motivation and decreased social activity.Thereforethatthe impact of thyroid dysfunction on a biopsychosocial characteristics, does not continue to secondarydiseases,efforts are needed to increase community awareness to recognize the signs and symptoms ofbiopsychosocialchanges. Therefore, the condition of iodine deficiency and excessive can be detected earlyandovercame with adequate therapy.